Substorm related changes in precipitation in the dayside auroral zone – a multi instrument case study - A. J. Kavanagh; F. Honary; I. W. McCrea; E. Donovan; E. E. Woodfield; J. Manninen; P. C. Anderson (Annales Geophysicae, 2002)
A period (08:10–14:40 MLT, 11 February 1997) of enhanced electron density in the D- and E-regions is investigated using EISCAT, IRIS and other complementary instruments. The precipitation is determined to be due to substorm processes occurring close to magnetic midnight. Energetic electrons drift eastward after substorm injection and precipitate in the morning sector. The precipitation is triggered by small pulses in the solar wind pressure, which drive wave particle interactions. The characteristic energy of precipitation is inferred from drift timing on different L-shells and apparently verified by EISCAT measurements. The IMF influence on the precipitation in the auroral zone is also briefly discussed. A large change in the precipitation spectrum is attributed to increased numbers of ions and much reduced electron fluxes. These are detected by a close passing DMSP satellite. The possibility that these ions are from the low latitude boundary layer (LLBL) is discussed with reference to structured narrow band Pc1 waves observed by a search coil magnetometer, co-located with IRIS. The intensity of the waves grows with increased distance equatorward of the cusp position (determined by both satellite and HF radar), contrary to expectations if the precipitation is linked to the LLBL. It is suggested that the ion precipitation is, instead, due to the recovery phase of a small geomagnetic storm, following on from very active conditions. The movement of absorption in the later stages of the event is compared with observations of the ionospheric convection velocities. A good agreement is found to exist in this time interval suggesting that E × B drift has become the dominant drift mechanism over the gradient-curvature drift separation of the moving absorption patches observed at the beginning of the morning precipitation event. Key words. Ionosphere (auroral ionosphere; particle precipitation) Magnetospheric physics (storms and substorms)